Enterovirus 71 Infection Cleaves a Negative Regulator for Viral Internal Ribosomal Entry Site-Driven Translation - Chen, Li-Lien (American Society for Microbiology, 2013)
Far-upstream element-binding protein 2 (FBP2) is an internal ribosomal entry site (IRES) trans-acting factor (ITAF) that negatively regulates enterovirus 71 (EV71) translation. This study shows that EV71 infection cleaved FBP2. Live EV71 and the EV71 replicon (but not UV-inactivated virus particles) induced FBP2 cleavage, suggesting that viral replication results in FBP2 cleavage. The results also showed that virus-induced proteasome, autophagy, and caspase activity co-contribute to EV71-induced FBP2 cleavage. Using FLAG-fused FBP2, we mapped the potential cleavage fragments of FBP2 in infected cells. We also found that FBP2 altered its function when its carboxyl terminus was cleaved. This study presents a mechanism for virus-induced cellular events to cleave a negative regulator for viral IRES-driven translation.